Psychological Abuse and Social Support in Chinese Adolescents: The Mediating Effect of Self-Esteem - Chen, Chen; Ji, Shengkai; Jiang, Juan (Frontiers in Psychology, 2022)
Although previous studies have explored relationships between psychological abuse and social support, the pathways from psychological abuse to social support are still unclear, particularly in Chinese adolescents. This cross-sectional study attempts to delineate the prevalence of psychological abuse, and to explore the relationships between psychological abuse, social support, and self-esteem under the Chinese cultural context. Data were obtained from 417 Chinese adolescents, aged 15-18 years old, and all of them completed the Child Psychological Abuse and Neglect Scale, Rosenberg Self-Esteem Scale (SES), and Multidimensional Scale of Perceived Social Support. Results indicated that the prevalence of psychological abuse in Chinese adolescents was 25.66%, and psychological abuse was negatively associated with self-esteem and social support, respectively. Self-esteem partially mediated the relationships between psychological abuse and social support. Findings highlight the importance of improving self-esteem in survivors of psychological abuse for decreasing the negative effects on social support. Additionally, the significance and limitations of the results were discussed.